Rapid mapping of urinary schistosomiasis: An appraisal of the diagnostic efficacy of some questionnaire-based indices among high school students in Katsina State, northwestern Nigeria. - Tolulope Ebenezer Atalabi; Taiwo Oluwakemi Adubi; Umar Lawal (Public Library of Science (PLoS), 2017)
BACKGROUND:In sub-Saharan Africa, over 200 million individuals are estimated to be infected with urinary and intestinal schistosomiasis. In a bid to lay a foundation for effective future control programme, this study was carried out with the aim of assessing the diagnostic efficacy of some questionnaire-based rapid assessment indices of urinary schistosomiasis. METHODOLOGY:A total number of 1,363 subjects were enrolled for the study. Questionnaires were administered basically in English and Hausa languages by trained personnel. Following informed consent, terminal urine samples were collected between 09:40 AM and 2:00 PM using clean 20 ml capacity universal bottles. 10μl of each urine residue was examined for the eggs of S. haematobium using x10 objective nose of Motic Binocular Light Microscope (China). PRINCIPAL FINDINGS:The average age ± Standard Deviation (SD) of school children examined was 15.30 ± 2.30 years and 40.87% were females. The overall prevalence and geometric mean intensity of S. haematobium infection were 26.41% (24.10─28.85) and 6.59 (5.59─7.75) eggs / 10 ml of urine respectively. Interestingly, a questionnaire equivalence of the prevalence obtained in this survey was 26.41% (24.10─28.85) for Rapid Assessment Procedure based on self-reported blood in urine. The results of correlation analyses demonstrated significant associations between the prevalence of S. haematobium infection and contact with potentially infested open water sources (r = 0.741; P = 0.006). By regression model, cases of respondents with self-reported blood in urine are expected to rise to 24.75% if prevalence of the infection shoots up to 26.5%. CONCLUSIONS/SIGNIFICANCE:The best RAP performance was obtained with self-reported blood in urine. Based on the overall prevalence value, the study area was at a "moderate-risk" of endemicity for urinary schistosomiasis. Chemotherapeutic intervention with Praziquantel, the rationale behind rapid assessment procedure for schistosomiasis, has been recommended to be carried out once in every 2 years for such communities.